Grammatical Errors of the Ninth-Grade Indonesian EFL Students’ Writing - Muharmah, Azzahra; Fauzan, Umar (EDUCASIA: Jurnal Pendidikan, Pengajaran, dan Pembelajaran, 2024)
Language serves as a crucial medium for communication, enabling the transmission of ideas and information. English, as a global lingua franca, plays a pivotal role in various domains, including trade, technology, academia, and diplomacy. The significance of English proficiency extends to its role as a medium of instruction in educational settings worldwide, facilitating access to global knowledge. Within English education, language acquisition encompasses four key skills: listening, speaking, reading, and writing. Among these, writing is often considered the most challenging skill due to its complex cognitive and linguistic demands. Writing requires mastery of grammatical rules, vocabulary, and formal aspects, which are essential for effective communication. Grammar, as the foundation of sentence structure, plays a critical role in ensuring clarity and coherence in written texts. This paper explores the challenges of writing in English, particularly in the context of grammatical errors in students' writing, and discusses the importance of understanding the components of language. The study also examines the writing process, emphasizing stages such as planning, drafting, editing, and finalizing, and highlights the distinction between errors and mistakes in language use. By focusing on grammatical errors and their sources, such as interlingual and intralingual transfer, the paper underscores the need for effective pedagogical strategies to improve students' writing skills. The analysis concludes that a comprehensive approach to language instruction, with a focus on grammar and writing structure, is crucial for enhancing students' proficiency in English writing.